In vitro and histological investigation of antitumor effect of some triazole compounds in colon cancer cell line - Parlak, Akif Evren; Tekin, Suat; Karatepe, Arzu; Koparir, Pelin; Telceken, Hafize; Ceribasi, Ali Osman; Karatepe, Mustafa (Wiley, 2019)
1,2,4-Triazoles are used as antifungal, antibacterial, antimicrobial, and antioxidant against some oxidative radical species. Recently, many 1,2,4-triazoles continue to be synthesized. In this study, the effect of the 1,2,4-triazole derivatives on human colon cancer (HT29) was investigated in vitro and in vivo in rats. MTT test was applied to in in vitro experiments. For in vivo study, rats were divided into seven groups as follows: Control group (negative control), azoxymethane (AOM), AOM+cisplatin 15, AOM+L1, AOM+L2, AOM+L3, and AOM+L4. To create colon cancer, the AOM injection was injected subcutaneously at a dose of 15mg/kg, three times (once weekly). The in vivo studies were completed at 28 weeks. It was found that the 1,2,4-triazole derivatives reduced the cell viability (P<0.05). In all animals in the experimental groups, mild dysplasia was detected in 100% of the colon mucosal epithelium. Severe dysplasia and adenocarcinoma were observed in L1 groups. As a result, this study determined that the 1,2,4-triazole derivatives exhibit antitumor activity.
Keywords: azoxymethane; colon cancer; HT29; 1; 2; 4-triazole